DSP-BASED SPECTROMETER FOR γ-RAY MEASUREMENT AND DETECTION - PHAM , NGOC TUAN; NGUYEN , NHI DIEN; DANG , LANH; TUONG , THI THU HUONG; NGUYEN , VAN HUNG; NGUYEN , DUC HOA; NGUYEN , AN SON (Nuclear Science and Technology, 2011)
Digital Signal Processing (DSP) is the advanced method for data processing coming from radiation detectors. A spectrometer for gamma detection was designed and used for nuclear physics experiments. All components of the spectrometer were designed, synthesized and created in one Xilinx FPGA device. The firmware was written in C-compiler from Keil, and the application software was written in LabView. The designed spectrometer is able to interface to PC through USB port, owning to EZ-USB device.